The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12035-013-8515-6
|View full text |Cite
|
Sign up to set email alerts
|

The Proform of Glia Cell Line-Derived Neurotrophic Factor: a Potentially Biologically Active Protein

Abstract: Growing evidences have revealed that the proforms of several neurotrophins including nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin-3 (NT3), by binding to p75 neurotrophin receptor and sortilin, could induce neuronal apoptosis and are implicated in the pathogenesis of various neurodegenerative diseases. The glial cell line-derived neurotrophic factor (GDNF), one of the most potent useful neurotrophic factors for the treatment of Parkinson's disease (PD), is firstly synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
1
15
0
1
Order By: Relevance
“…36 Neurotrophins are translated as large (130 kDa) propolypeptides, known as pro-forms, that undergo posttranslational proteolytic cleavage to exert their neuroprotective function. 39 Pro-forms have been shown to preferentially activate p75 NTR to mediate apoptosis, whilst activation of TrK receptors by mature forms promote survival. This is illustrated by observations with the pro-forms of NGF, BDNF and NT3, which have a high-affinity ligand for p75 NTR .…”
Section: Müller Glia Are An Important Source Of Neurotrophins Within mentioning
confidence: 99%
See 2 more Smart Citations
“…36 Neurotrophins are translated as large (130 kDa) propolypeptides, known as pro-forms, that undergo posttranslational proteolytic cleavage to exert their neuroprotective function. 39 Pro-forms have been shown to preferentially activate p75 NTR to mediate apoptosis, whilst activation of TrK receptors by mature forms promote survival. This is illustrated by observations with the pro-forms of NGF, BDNF and NT3, which have a high-affinity ligand for p75 NTR .…”
Section: Müller Glia Are An Important Source Of Neurotrophins Within mentioning
confidence: 99%
“…Upon binding to this receptor, these neurotrophins form a heterotrimeric complex that has a marked proapoptotic effect in opposition to their mature forms. 39 NGF, BDNF and NT3 have been shown to be secreted as pro-forms and cleaved extracellularly by proteases into the mature forms. 39,40 As part of their neuroprotective function, Müller glia produce selective neurotrophins under different conditions.…”
Section: Müller Glia Are An Important Source Of Neurotrophins Within mentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF acts on neurons, supporting their survival, proliferation and differentiation. The recent findings have suggested that astrocytes produce BDNF (Girardet et al, 2013; Sun et al, 2014). Overexpressing BDNF in astrocytes, Quesseveur and colleagues examined behavioral outcomes of the altered neurons-to-astrocytes BDNF ratio.…”
Section: Animal Models Of Astrocyte Dysfunctionmentioning
confidence: 99%
“…Quantification of protein bands was performed by means of volume densitometry using program Scion Image (Scion Corporation, http://www.scioncorp.com). proGDNF was detected at 38 kDa (Sun et al ., ), mature GDNF dimer was detected at 28 kDa (Lin et al ., ; Euteneuer et al ., ), mature GDNF monomer was detected at 24 kDa (according to the antibody manufacturer) (Fig. ) and β‐tubulin was detected at 50 kDa.…”
Section: Methodsmentioning
confidence: 99%